Mamee Chef - Zulkifli, Muhammad Zamer (Universiti Teknologi MARA, Perak, 2022)
Mamee Chef is a Malaysian instant noodle. Mamee Chef’s premium instant noodles use a Pull Noodles firmer and springier. With the addition of tasty ingredients and vegetables, the technology enhances the irrestistible ultimate taste of it.